Impact of long-term civil disorders and wars on the trajectory of HIV epidemics in sub-Saharan Africa - David Gisselquist (Taylor & Francis Group, 2004)
From the mid-1970s, seven countries in sub-Saharan Africa have experienced civil disorders and wars lasting for at least 10 years. In two - Sierra Leone during 1991-2002, and Somalia from 1988 and continuing - adult HIV prevalence remained below 1%. In the Democratic Republic of the Congo, HIV prevalence appears to have stabilised during post-1991 civil disorder and war. Limited information from Angola (civil war 1975-2002) and Liberia (civil disorder and war from 1989 and continuing) suggests low HIV prevalence. Mozambique's HIV prevalence was near 1% after its 1975 - 1992 civil war, but increased dramatically in the first post-war decade. Across African countries with long-term wars, HIV seems to have spread more slowly than in most neighbouring countries at peace. This evidence contributes to the ongoing debate about the factors that explain differential epidemic trajectories, a debate which is crucial to the design of HIV prevention programmes. One possible explanation for slow epidemic growth in wartime is that unsterile health care accounts for an important proportion of HIV transmission during peacetime, but much less when wars disrupt health services. However, other explanations are also possible. The roles of sex and blood exposures in HIV epidemics in war and peace await empirical determination.